Research progress of assessment tools for Parkinson’s disease psychosis in China - Shuchan Wang; Baoqin Yang; Ping Lu; Yaping Chen; Jianing Dai; Lijun Zhao; Miaomiao Wang; Jiahuan Yu; Lixiu Zhang (Frontiers in Psychiatry)
Parkinson’s disease psychosis (PDP) has a significant impact on the quality of life and disease prognosis of patients with Parkinson’s disease (PD). Accurate assessment of psychotic symptoms in PD patients is critical for early detection and intervention. This, in turn, improves clinical outcomes and quality of life. This review evaluates both internationally validated and China-specific assessment tools for PDP, including the Parkinson’s Psychosis Questionnaire, Geriatric Apathy Scale, and culturally adapted instruments. We analyze the psychometric properties, cultural applicability, and clinical utility of these tools in Chinese populations. Our findings provide evidence-based recommendations for healthcare professionals to optimize tool selection, enhance diagnostic accuracy, and guide targeted interventions in China’s diverse clinical settings. The review also identifies gaps in current assessment approaches and proposes directions for future tool development and validation studies.